Efficacy and safety of oral ciprofloxacin for treatment of serious urinary tract infections. - Fass, R J (1987)
Eighty-three patients with serious urinary tract infections were treated with oral ciprofloxacin. Of these patients, 79 were hospitalized, and 41 had known structural or neurologic abnormalities of the urinary tract. The most common pathogens were members of the family Enterobacteriaceae (MICs, less than or equal to 0.06 microgram/ml), Pseudomonas aeruginosa (MICs, 0.13 to 2 micrograms/ml), and Enterococcus faecalis (MICs, 0.5 to 2 micrograms/ml). Sixty-eight patients were able to be evaluated for determining efficacy; all responded symptomatically, and all urinary pathogens were eradicated on days 3 to 5 of treatment. Five patients, who were treated for a relatively short duration (2 to 10 days), relapsed 5 to 9 days posttreatment. Six patients became colonized with yeasts during treatment, and seven patients developed bacterial reinfections 5 to 9 days posttreatment. All patients whose infections relapsed or who developed infections with new organisms had neurogenic bladders, structural abnormalities of the genitourinary tract, or urinary catheters. There was no instance of bacteria developing resistance during treatment. Ciprofloxacin probably caused nausea with or without vomiting in 7 of the 83 patients, headache in 3 patients, and mild elevation of hepatic enzymes in 2 patients; other adverse reactions were observed but were probably not drug related. Oral ciprofloxacin was effective and safe for the treatment of serious urinary tract infections caused by a variety of bacterial pathogens.